Uplift response of irregular-shaped anchor in cohesionless soil - Niroumand, Hamed (King Fahd University of Petroleum and Minerals, 2014)
This paper presents an innovative soil anchor in loose and dense sand. Many studies on the anchor plates, both theoretical and experimental, have been conducted, although the existing works were mainly performed on regular and symmetrical anchor plates. A new anchor system is an irregular and non-symmetry shape anchor. This is an innovative system due to the special shape and the penetration into soils. Two sizes of irregular-shaped anchors, 159 and 297 mm, were used. The non-symmetry anchor employed in the system contributes to its good performance and high pullout load capacity. The maximum resistance increased based on the embedment ratio and the density of the sand. An important innovation of this system is the installation method, where it does not require excavation and grouting. The main objective of this research is to validate the break-out factors and the ultimate uplift capacity load of the irregular-shaped anchor with the existing researches related to anchor plates. The experimental research was performed on the models in a chamber box. For the 159 mm-width irregular-shaped anchor, an embedment ratio L/D between 1 and 7 and for the 297 mm-width embedment ratio L/D between 1 and 4 were employed. The irregular-shaped anchors were used in dry, loose and dense sand. The new irregular-shaped anchors are compatible with the symmetrical anchor plates as determined by existing researchers.